Testing the “critical-size” in calvarial bone defects: revisiting the concept of a critical-sized defect (CSD) - Cooper, Gregory M. (2010)
BACKGROUND: There is a clinical need for bone replacement strategies because of the shortfalls endemic to autologous bone grafting, especially in the pediatric patient population. For the past 25 years, the animal model that has been used to test bone replacement strategies has been the calvarial critical-sized defect (CSD), based on the initial size of the bone defect. This study was undertaken to test the concept of the critical-size in several different models. A review of the theoretical and scientific bases for the CSD was also undertaken. METHODS: Two different rodent species (including 28 adult mice and 6 adult rats) were used to assess bone healing via 2D radiographic analysis after creating small bone defects using different surgical techniques. RESULTS: Defects in mice that were smaller than critical-sized (1.8mm diameter) were shown to heal a maximum of 50% one year postoperatively. Small (2.3mm diameter) defects in the rat skull showed approximately 35% healing after 6 weeks. Neither the choice of rodent species nor the maintenance of the dura mater significantly affected calvarial bone healing. CONCLUSIONS: These results suggest that calvarial bone healing is not well described and much more data needs to be collected. Also, after a review of the existing literature and a critique of the clinical applicability of the model, it is suggested that the use of the term “critical-sized defect” be discontinued.